2009
DOI: 10.1039/b814742f
|View full text |Cite
|
Sign up to set email alerts
|

Noble metal ionic catalysts: correlation of increase in CO oxidation activity with increasing effective charge on Pd ion in Pd ion substituted Ce1−xMxO2−δ(M = Ti, Zr and Hf)

Abstract: Pd ion substituted Ce1-xMxO2-delta (M = Ti, Zr, Hf) have been prepared by a single step solution combustion method. Two atom% Pd ion substitution in the title compounds is confirmed by X-ray diffraction (XRD) and Pd ion charge state and redox properties have been determined by X-ray photoelectron spectroscopy (XPS) and H2/TPR studies. While Pd ion in CeO2 (Ce0.98Pd0.02O2-delta) showed higher catalytic activity for CO oxidation than Pd metal impregnated over CeO2, further increase in the catalytic activity is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…It has been found that activation energy decreases with increase in the effective charge on Pd ion in these oxides [74]. There are also points to note that in general, CO oxidation rates with metal ionic catalysts are higher by 20-30 times compared with the same amount of metal impregnated catalysts.…”
Section: Catalytic Activities Of Noble Metal Ion Substituted Ceo 2 Camentioning
confidence: 96%
See 1 more Smart Citation
“…It has been found that activation energy decreases with increase in the effective charge on Pd ion in these oxides [74]. There are also points to note that in general, CO oxidation rates with metal ionic catalysts are higher by 20-30 times compared with the same amount of metal impregnated catalysts.…”
Section: Catalytic Activities Of Noble Metal Ion Substituted Ceo 2 Camentioning
confidence: 96%
“…Noble as well as transition metal ion substituted CeO 2 catalysts such as Ce 0.67 Cr 0.33 O 2+ı , Ce 1−x Ru x O 2−ı , Ce 1−x Fe x O 2−ı and Ce 1−x Pt x O 2−ı have been synthesized by hydrothermal and sonochemical methods, respectively [60][61][62][63]. Table 1 compiles metal ion substituted CeO 2 materials prepared by solution combustion, hydrothermal and sonochemical methods [33,[50][51][52][53][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Synthesis and Structure Of Noble Metal Ion Substituted Ceo 2mentioning
confidence: 99%
“…The remarkably high performance of Pd/CeO 2 catalysts in oxidation reactions is caused by the strong interaction between palladium and cerium oxide 8,21 . The metal-support interaction in Pd/CeO 2 catalysts has been studied in many works 4,9,23,[28][29][30][31][32][33][34][35][36][37][38][39] . The metal-support interaction in Pd/CeO 2 catalysts has been studied in many works 4,9,23,[28][29][30][31][32][33][34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…Dissociative adsorption of H 2 O and CO 2 resulted in the release of H 2 and CO while the surface reactions between the adsorbed species resulted in release of CO 2 and H 2 O. Substitution of Zr and Ti is beneficial as the bulk substitution of these elements results in an enhanced oxygen storage capacity 30,31 and, hence, enhanced redox couples are expected.…”
Section: Structural Studiesmentioning
confidence: 93%